Cleansing the world of the germ of laziness: hygiene, sanitation, and the Javanese population in Suriname - Rosemarijn Hoefte (História, Ciências, Saúde: Manguinhos, 2014)
In 1915 the Rockefeller Foundation took its hookworm eradication campaign to Suriname, but was soon disappointed because of opposition from its main target group: the Javanese. Moreover, authorities and planters objected to the construction of latrines because of the costs and their belief that the Javanese were “unhygienic”. In describing the labor migration from Java to Suriname, I show that this “lack of hygiene” was closely related to the system’s organization. I argue that uncleanliness was the consequence of harmful socio-economic and ecological conditions. Secondly I suggest that even though the Foundation did not manage to cleanse Suriname of hookworm, its educational efforts, its emphasis on prevention, and its training of local health workers probably had more impact than Rockefeller officials thought.